Entrepreneurial Use of Gamification for Knowledge Sharing inside Organization; A Public Service Media from Middle East (2021)
Knowledge as an organizational resource in media businesses has become increasingly important in a competitive environment. There is a growing interest in developing new techniques to enhance knowledge sharing between people, that is conducive to media entrepreneurs. One of the main barriers to knowledge sharing in communicating entrepreneurs is the lack of motivation which can be improved by using gamification. The aim of this research is to achieve a better understanding of the gamified knowledge sharing process to improve organizational entrepreneurship among TV employees. We conducted semi-structured interviews with 15 employees and managers of the IRIB organization. Qualitative analysis of the research data was conducted in three steps: transcribing data, coding and organizing categories. Most of IRIB’s employees inspired by intrinsic motivations include status, power, learning, autonomy, and community. Security is the only and most critical extrinsic motivation in IRIB organization. Moreover, we have found four categories of user types, namely achiever, socializer, discoverer, and survivor. Our study identified the main motivators of media staff that create a sense of happiness and motivation to participate in organizational entrepreneurship via knowledge sharing. Finally, we offer new insights about the media employees’ user types in the gamified knowledge sharing system.